The last lecture - Pausch, Randy (Hyperion Books, 2008)
Reflections of a Carnegie Mellon computer science professor who lectured on "Really achieving your childhood dreams," shortly after having been diagnosed with terminal cancer. His advice concerned seizing the moment while living, rather than dying.